KARAKTERISTIK PASIEN DIABETES MELITUS TIPE II DI PUSKESMAS CILACAP TENGAH 1 DAN 2 - Prasetyani, Dewi; Apriani, Evy (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Diabetes type 2 patients continues to increase. Health research results show that there is currently no difference in the number of DM patients between urban and rural communities. The results also show that many DM patients who are still in productive age. Likewise with other factors such as gender, knowledge and education. The success of DM management is influenced by the ability of patients to perform self-care activities to keep blood sugar level within normal limits. The purpose of the study: the study was to describe the characteristics of type 2 DM patients consisting of age, gender, education, occupation, income, duration of DM, knowledge and self-care ability. Type of research: the research used descriptive survey research. A total of 152 people were determined using total sampling technique. The instrument of the research is questionnaire about demographic data of respondent, knowledge and ability of self-care. Data analysis uses the mean, minimum, maximum, standard deviation and frequency distribution. Result: the average of the respondent have age 60,8 year. The majority of respondent were 101 women (66,4), high school or college education level of 78 people (51,3). Most of the work was retired respondent or housewives is as many as 129 people (84,9%). Most of the respondent had an income of more than and equal to the UMR89 people (58,6%). The average DM experience was 5 years. The level of knowledge about DM is mostly in the good category that is 85 people (55,9%). Most respondent have bad self-care ability that is 86 people (56,6%). Keywords: type 2 diabetes mellitus, characteristics